The Urgency of Establishing a World Class Takāful Operator in Indonesia: Reason and Concept - Rahman, Wahyudin; Fatwa, Nur (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2022)
This study analyzes the urgency of establishing a World Class Takāful Operator(WCTO), initiated by the National Committee on Islamic Finance and Economics (KNEKS). This is due to several reasons, including a deadline for work plans and the separation of Sharia Units in 2024, risk mitigation support to Bank Syariah Indonesia (BSI), preparation of the ASEAN Framework Agreement On Services (AFAS) in 2025, strengthening halal value chain and improvement of the national insurance image. Using qualitative descriptive analysis, this study recommends the ideal concept (models, mechanisms, market segmentation and distribution channels) for WCTO formation. The ideal concept for WCTO requires the combination of social and commercial insurance, consolidation with portfolio transfers, retail and corporate balance and existing distribution channels with digitalization. This finding becomes a new insight into takafful literature. AbstrakPenelitian ini menganalisis urgensi pembentukan Class Takāful Operator (WCTO) yang telah di inisiasi Komite Nasional Keuangan dan Ekonomi Syariah (KNEKS). Hal ini karena adanya batas waktu rencana kerja dan pemisahan Unit Syariah tahun 2024, dukungan mitigasi risiko kepada Bank Syariah Indonesia (BSI), persiapan ASEAN Framework Agreement On Services (AFAS) tahun 2025, penguatan rantai nilai halal dan meningkatkan citra asuransi nasional. Dengan analisis deskriptif kualitatif, penelitian ini merekomendasikan konsep ideal (model, mekanisme, segmentasi pasar dan jalur distribusi) pembentukan WCTO. Adapun konsep ideal WCTO dilakukan dengan kombinasi asuransi sosial dan komersial, konsolidasi dengan transfer portofolio, perimbangan retail dan korporasi dan existing jalur distribusi dengan digitalisasi.